The integration of multimedia elements in classroom teaching among TESL teacher-trainees [electronic resource] - 436951 Siti Suhaida Shukor; Fakulti Pendidikan (2009)
Project Paper Sarjana Muda (Sains serta Pendidikan (TESL) - Universiti Teknologi Malaysia,2009